STRATEGI BIMBINGAN BELAJAR PRIVATE DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA BIMBINGAN BELAJAR GEN Z EDUCATION - Aprilia Wulandari; Eva Dwi Agustina; Intan Nirmalasari Rizki Anjarwati; Munip Abdillah; Nabil Salsabila (STKIP Pesisir Selatan, 2026)
Low motivation and learning outcomes of students at school are crucial problems that affect the success of the educational process. Students who have high motivation to learn tend to be more active, and enthusiastic in following the learning process. On the other hand, students who have low motivation to learn tend to show less attention to the learning process so that they do not understand the material presented. This study aims to analyze learning strategies in private tutoring and its impact on improving student motivation and learning outcomes. The background of this research is based on students' needs for more intensive learning assistance outside the school environment, as well as the existence of various obstacles faced in the learning process, such as low motivation and lack of understanding of students in the learning material. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the application of appropriate learning strategies, such as a solution-based approach (Solution-Focused Brief Counseling), understanding of student learning characteristics and styles, and the development of emotional relationships between teachers and students, are able to increase motivation, confidence, and active involvement of students in the learning process and optimal learning outcomes.